1995
DOI: 10.1210/jcem.80.10.7559865
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and bone turnover before and after surgical cure of Cushing's syndrome.

Abstract: We measured bone mineral density (BMD) using dual-energy x-ray absorptiometry in 20 patients with Cushing's syndrome (CS) (14 preand 2 postmenopausal women, 4 men) before and in 18 of them also at regular intervals after surgical cure (median duration of follow-up, 36 months). In addition, in the premenopausal women with CS, fast ing blood samples and 2-h fasting urine samples for measurement of biochemical parameters of bone and collagen metabolism were col lected before and in 9 of them also at regular inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
61
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 13 publications
9
61
0
3
Order By: Relevance
“…The median (interquartile rage) time in remission was 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years. Nineteen (38%) patients were receiving GC replacement therapy: ten after bilateral adrenalectomy, seven due to pituitary insufficiency after transsphenoidal pituitary surgery and/or radiotherapy and two after unilateral adrenalectomy.…”
Section: Hormonal Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (interquartile rage) time in remission was 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years. Nineteen (38%) patients were receiving GC replacement therapy: ten after bilateral adrenalectomy, seven due to pituitary insufficiency after transsphenoidal pituitary surgery and/or radiotherapy and two after unilateral adrenalectomy.…”
Section: Hormonal Statusmentioning
confidence: 99%
“…Prospective studies have demonstrated improved BMD following treatment of CS (12,13,14). However, these studies have small numbers of patients, short follow-up time and/or lack a control group.…”
mentioning
confidence: 99%
“…Bone formation, evaluated most frequently with osteocalcin (OC) measurements, was found to be greatly suppressed in most [3][4][5][6][7] but not all studies [8][9][10], while aminoterminal propeptide of type 1 procollagen was less suppressed or even normal in these patients. On the other hand, conflicting data have been reported on the rate of bone resorption in patients with endogenous hypercortisolism, as resorption markers have been found to be normal [5,6,11], decreased [6,7,12], and even increased [9,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While most authors showed an increase in BMD at most skeletal sites and in the total skeleton [8,10,[16][17][18][19] accompanied with a rapid increase in serum OC levels, the exact time course of these changes has not been explored yet. Using dual photon X-ray absorptiometry, our recent study indicated a redistribution of bone mineral content from the peripheral to the axial skeleton after the cure of CS [19].…”
Section: Introductionmentioning
confidence: 99%
“…GC administration causes bone loss and an increase in bone fragility, resulting in a great increase in fracture risk [1][2][3][4][5]. Excessive intrinsic GC due to Cushing's syndrome is associated with increased bone resorption markers, decreased bone mineral density (BMD) and increased fracture risk [6][7][8][9][10]. However, a metaanalysis of prior GC use and fracture risk suggested that fracture risk was explained only partly by BMD [3].…”
Section: Introductionmentioning
confidence: 99%